「以友輔仁」新詮：羞恥在Aristotle友愛觀中的積極意義 A New Interpretation of Fostering Virtue Through Character Friendship: Significance of Shame in Aristotle's Idea of Friendship - 陳伊琳 Yi-Lin Chen (National Taiwan Normal University, 2023)
朋友如何發揮輔助彼此品德修養的功能？以友輔仁的確實機制為何？本文旨在探討 Aristotle觀點下羞恥的德育價值以及「在朋友面前感到羞恥」的積極意涵。首先指明羞恥是對不名譽的恐懼，若稱具有羞恥心的人則表示其已經內化一套社會的是非善惡觀。因此，羞恥是值得在德育上培養的可欲的道德情緒。就Aristotle發展論的德育觀而言，羞恥扮演個體道德發展上承先啟後的樞紐角色。本文嘗試闡明「以友輔仁」的具體機制之一便是藉由「在朋友面前感到羞恥」彰顯出來的，這是透過與德行之友的安穩交心對話，將先前經由習慣養成的德行付諸理性檢驗，此即「德行重估」，透過雙方實踐智慧的運用將習俗性羞恥轉變為真羞恥，若然，原先他人眼中的不光彩便轉換為個人眼中的不光彩，他律性的羞恥轉變為自律的羞恥。此課題的探討有望回應R. S. Peters提出的「道德教育的弔詭」，釋明從道德他律到自律的「過渡」如何可能。實務性價值在於闡明羞恥的德育價值，以及以友輔仁的運作機制。 This study focuses on addressing the following questions: How do friends help each other to improve character? What is the exact mechanism by which virtue is fostered through character friendship? From an Aristotelian perspective, this study investigates the moral value of shame. Shame is argued to be a desirable moral emotion worth developing. As a distinctive type of fear, shame reflects the fear of dishonor and disgrace caused mostly by one's own voluntary actions as well as those of significant others. Aristotle analyzed shame in detail in terms of its eliciting causes, intentional objects, and personal feelings. Different from other emotions that are aroused directly by the confronting situation, shame is normally felt in front of other people. As the proverb goes, "Shame dwells in the eyes." Specifically, the eyes literally refer to the witnessing by the surrounding people and figuratively signify the negative judgment made by other people on an individual's actions. Thus, shame is not a moral virtue in itself. Precisely, shame is an intermediate emotional state between two extremes (i.e., bashfulness and shamelessness) and can be regarded, at best, as a quasi-virtue, in that it helps to constrain the actions of modest people. Therefore, shame is considered to be conditionally good, but not good without qualification. After clarifying the nature of shame, Aristotle emphasizes that the development of shame as a moral emotion is worthwhile among young people because shame symbolizes a watershed and a critical turning point in one's virtue development. From an Aristotelian developmental perspective of the inculcation of virtues, a young child is incapable of listening to and understanding rational argument and teaching; therefore, virtue education must begin with cultivating their "noble joy" and "noble hatred" through proper habituation of both virtuous emotions and actions. In so doing, their inborn, primitive, basic pleasures, and pains are gradually transformed and broadened, and by being led to attend to certain morally significant information and read it properly, more sophisticated and appropriate joys and hatred come into being. Among the various emotions, shame is a noble hatred, especially for one's voluntary disgraceful bad behavior. As soon as an individual develops shame, it indicates that they have successfully internalized a social measure of differentiating right from wrong. At this juncture, the conventional concept of good and evil is established in their mind. The standard of social honor and the moral emotion of shame can be perceived as being two sides of the same coin. According to Colby and Kohlberg's characterization of Aristotle's stage theory of virtue development, "shame ethics" goes above and beyond the previous "fear ethics," in that as a distinctive species of the main genus of fear, shame is not a fear of personal corporal pain but a fear of disgrace resulting from the transgression of social order. Nevertheless, for Aristotle, the goal of virtue development is full virtue interwoven with practical wisdom. The issue of concern is how the habituated virtue could be converted into full virtue. This question reflects R. S. Peters's well-known "the paradox of moral education" to the effect that the goal of moral education is to develop an individual conducting themself rationally, intelligently, and autonomously, but the brutal fact of human psychology is that a young child is impervious to this form of education and instead the child must be raised through habituation, namely by following conventional behavior and tradition. In brief, in Peters's famous words, "they can and must enter the palace of Reason through the courtyard of Habit and Tradition." Are reason and habit compatible? How can the goal of rational morality be accomplished through habituation? In addition to the interpretation by N. Sherman of the very nature of habituation as a type of "critical practice, which dispels the misgiving that habituation and reason are incompatible, this study argues that Aristotle's detailed analysis of shame in general and his notion of "shame before character friendship" in particular explains how the "habituated virtue" can be converted into full virtue through the critical examination of character friends' practical wisdom. Specifically, this study describes the significant and positive meaning of "feeling shame before character friendship." "Shame before character friendship" is argued to play a pivotal role in converting conventional shame into real shame. Conventional shame refers to feelings about bad things or evils defined by social conventions; real shame refers to feelings about genuine faults recognized by one's practical wisdom. The mechanism by which full virtue is fostered through character friendship involves people feeling free to talk to each other, exchange ideas, and critically scrutinize their respective habituated virtues. Specifically, character friendship is developed between two virtuous people who love each other and wish well for each other's virtue development. They enjoy living together by spending time on performing virtuous actions and having rational dialogues. In this manner, the so-called "virtue reassessment" occurs. That is, two virtuous friends freely and critically scrutinize the reasonableness and rational ground of their habituated virtues and their associated conventional shame. Thus, shame stops a person from dwelling in the eyes of others but dwelling in their own eyes. That is, bad things and evils are now measured by one's own standard of value rather than the previously internalized traditional social standard of honor. This discussion on Aristotle's distinction of two types of shame and his elaboration on the special meaning of "shame before character friendship" can hopefully be a response to Peters's "the paradox of moral education," elaborating how the transition from moral heteronomy and habituated virtue to moral autonomy and full virtue is possible. That is, the long-standing paradox of moral education is resolvable from Aristotelian perspective. In addition, the discussion has practical educational implications for explaining the moral value of cultivating the moral emotion of shame and developing character friendship.